First draft genome of Thecaphora frezii, causal agent of peanut smut disease - Renee S. Arias; Cinthia Conforto; Valerie A. Orner; Edgardo J. Carloni; Juan H. Soave; Alicia N. Massa; Marshall C. Lamb; Nelson Bernardi-Lima; Alejandro M. Rago (BMC Genomic Data, 2023)
Abstract Objectives The fungal pathogen Thecaphora frezii Carranza & Lindquist causes peanut smut, a severe disease currently endemic in Argentina. To study the ecology of T. frezii and to understand the mechanisms of smut resistance in peanut plants, it is crucial to know the genetics of this pathogen. The objective of this work was to isolate the pathogen and generate the first draft genome of T. frezii that will be the basis for analyzing its potential genetic diversity and its interaction with peanut cultivars. Our research group is working to identify peanut germplasm with smut resistance and to understand the genetics of the pathogen. Knowing the genome of T. frezii will help analyze potential variants of this pathogen and contribute to develop enhanced peanut germplasm with broader and long-lasting resistance. Data description Thecaphora frezii isolate IPAVE 0401 (here referred as T.f.B7) was obtained from a single hyphal-tip culture, its DNA was sequenced using Pacific Biosciences Sequel II (PacBio) and Illumina NovaSeq6000 (Nova). Data from both sequencing platforms were combined and the de novo assembling estimated a 29.3 Mb genome size. Completeness of the genome examined using Benchmarking Universal Single-Copy Orthologs (BUSCO) showed the assembly had 84.6% of the 758 genes in fungi_odb10.